Relations among motor abilities and skills in handball - Gruic, I. (Proceedings of the 7th International Conference on Sport Sciences Research and Technology Support, 2019)
The objective of the research was to determine the relationship between motor abilities and levels of acquisition of certain specific motor skills. On 80 students / adults who participated, with average (X1±SD) age of x=19 years, mass of 76±3.5 kg,179±4.7 cm tall, standard tests for the assessment of anthropometric characteristics, basic and specific motor abilities, and motor skills in performing different handball techniques were assessed. Statistically significant relations between abilities and skills were determined, especially among the speed, precision and technique of performing the shooting techniques in handball.